2022
DOI: 10.3389/fcimb.2022.758745
|View full text |Cite|
|
Sign up to set email alerts
|

Antagonistic Coevolution Limits the Range of Host Defense in C. elegans Populations

Abstract: Host populations often evolve defenses against parasites due to the significant fitness costs imposed by infection. However, adaptation to a specific parasite may alter the effectiveness of the host’s defenses in general. Consequently, the specificity of host defense may be influenced by a host population’s evolutionary history with parasites. Further, the degree of reciprocal change within an interaction may profoundly alter the range of host defense, given that antagonistic coevolutionary interactions are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…These results would seem to support our model, showing that general resistance is favored in the face of rapid coevolution. However, more recently, Lewis et al (2022) found the opposite trend, where Caenorhabditis elegans coevolved with a bacterial pathogen were more susceptible to foreign strains than the control hosts. In all cases however, the underlying infection genetic system is not known, making it challenging to draw direct comparisons with theory.…”
Section: Discussionmentioning
confidence: 97%
“…These results would seem to support our model, showing that general resistance is favored in the face of rapid coevolution. However, more recently, Lewis et al (2022) found the opposite trend, where Caenorhabditis elegans coevolved with a bacterial pathogen were more susceptible to foreign strains than the control hosts. In all cases however, the underlying infection genetic system is not known, making it challenging to draw direct comparisons with theory.…”
Section: Discussionmentioning
confidence: 97%